Minimally invasive surgery for the management of iatrogenic colon perforation in the elderly - Dagmura, Hasan; Daldal, Emin; Bakir, Huseyin; Akbas, Ahmet; Dasiran, Fatih; Okan, Ismail (Annals of Medical Research, 2021)
Aim: Colonoscopy is the most commonly used diagnostic tool for screening for colorectal cancer in asymptomatic individuals and for surveillance in patients with a history of colonic disease. The procedure has several drawbacks, including acute colon perforation. As elderly individuals with aging immune systems frequently respond inadequately to physiologic stress, this life-threatening complication requires meticulous management in this patient cohort. We aimed to evaluate a minimally invasive surgical approach to iatrogenic colon perforation (ICP) in this vulnerable age group.Material and Methods: This is a retrospective study. We reviewed data from all patients ≥ 65 years of age diagnosed with iatrogenic colon perforation (ICP) between January 2012 and June 2019 at Gaziosmanpaşa University Hospital. Results: Seventeen cases of ICP were identified (mean age was 76.5 years); 16 patients were treated surgically and one was managed conservatively. The most frequent site of perforation was the sigmoid colon (58.8%) and surgical management was primarily laparoscopic (93.7%). Twelve of the 16 patients who were managed with surgical intervention underwent laparoscopic primary repair and three patients underwent laparoscopic colectomy due to a primary diagnosis of colorectal malignancy. One patient with delayed diagnosis underwent laparotomy and proctosigmoidectomy (Hartmann procedure); this patient did not survive beyond the immediate post-operative period.Conclusion: Our findings suggest that early recognition is critical for the successful treatment of ICP in the elderly. Most patients respond well to a minimally invasive laparoscopic approach. This approach can be considered for large perforations and is safe and effective when carried out by an experienced surgeon.
Keywords: Colonoscopy; geriatric; intestinal perforation; laparoscopy; minimally invasive surgery